Optimalisasi Kemampuan Literasi Digital Mahasiswa dengan Pemanfaatan Renderforest.com - Nuraina, Nuraina; Rohantizani, Rohantizani; Hayati, Rahmi (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2025)
Digital literacy is an essential skill that students must possess to navigate the challenges of the digital era. It encompasses the ability to utilize technology to support learning, work, and creative activities. However, several studies indicate that many students still face limitations in the digital literacy skills required to participate optimally in today’s world. This Community Service Program was designed to enhance students’ digital literacy by providing training on the use of Renderforest.com, an online platform offering services for creating animated videos, graphic designs, and digital marketing materials. The participants consisted of 30 seventh-semester students from the Mathematics Education Study Program, Faculty of Teacher Training and Education, Universitas Malikussaleh. This training was conducted over two days with a total duration of 4 hours per day. The implementation methods included delivering instructional materials, hands-on practice in creating accounts and exploring Renderforest.com’s features, group discussions, and evaluation of the digital products produced by the students. The results show that 90% of the students successfully mastered Renderforest.com’s basic features, 88% demonstrated high motivation and enthusiasm, and 85% gained an understanding of the importance of digital literacy for supporting their learning and career readiness. In conclusion, the training proved effective in improving students’ digital literacy skills while equipping them with competencies that are highly relevant to the demands of the current digital age.